Putting Institutions at the Centre of Primary Health Care Reforms : Experience from Implementation in Three States in Nigeria - Odutolu, Oluwole; Ihebuzor, Nnenna; Tilley-Gyado, Ritgak; Martufi, Valentina; Ajuluchukwu, Michael; Olubajo, Olalekan; Banigbe, Bolanle; Fadeyibi, Opeyemi; Abdullhai, Rabiya; Muhammad, Ado J.G. (Taylor and Francis, 2016)
Within the last two decades, the Nigerian government has committed to strengthening its primary health care system, through reforms addressing institutional restructuring, deepening decentralized governance, and the incorporation of an alternative health care financing strategy. One of these reforms prescribed the establishment of state primary health care agencies/boards (SPHCDBs) as an integral part of the national health system, with the principal responsibility “for the coordination of planning, budgeting, provision and monitoring of all primary health care services that affect residents of the state.” Central to this reform is the integration of primary health care (PHC) governance and management, popularly called primary health care under one roof. Another reform, piloting results-based financing, has been implemented since 2011 in three states under the Nigeria State Health Investment Project. This study assesses the implementation of the Primary Health Care Under One Roof (PHCUOR) policy as part of the broader PHC reforms, with a specific focus on how this policy has been strengthened through the Nigeria State Health Investment Project (NSHIP) in Adamawa, Nasarawa, and Ondo states, documenting the evolution of SPHCDB and PHC service delivery, with a focus on management, accountability, and incentives. The study shows that, in the above-mentioned states, significant milestones were achieved in the establishment of the SPHCDB, the strengthening of PHC systems, the improvement of accountability linkages, and an increase in service utilization. The authors therefore argue that integrated PHC systems through SPHCDBs, as enshrined in the PHCUOR guidelines, are a panacea for effective provision of primary health care and a potential game changer for health outcomes, especially when reinforced with a results-based financing approach.